Effectiveness of a community‐based responsive feeding programme in rural Bangladesh: a cluster randomized field trial - Aboud, Frances E. (Matern Child Nutr, 2008)
Responsive complementary feeding, whereby the mother feeds her child in response to child cues of hunger state and psychomotor abilities, is a problem in some countries, and likely contributes to malnutrition. Interventions are needed to evaluate whether promoting responsive feeding would add any benefit. Using a cluster randomized field trial, we evaluated a six‐session educational programme that emphasized practice of two key behaviours, namely child self‐feeding and maternal responsiveness. One hundred mothers and their 12‐ to 24‐month‐olds attended the sessions as part of village clusters randomly assigned to the intervention group. A similar number of controls received sessions on foods to feed and nutritional disorders. Outcomes assessed at pre‐test, 2‐week post‐intervention and again 5‐months post‐intervention included weight, mouthfuls of food taken, self‐feeding and maternal responsiveness. Research assistants, blind to group assignment, observed and coded mother and child behaviours during the midday meal. Secondary measures included foods fed and feeding messages recalled. Analysis was based on intention to treat and accounted for clustering. Only 10% of each group was lost to follow‐up. Weight (d = 0.28), weight gain (d = 0.48) and child self‐feeding (d = 0.30) were significantly higher in the responsive feeding group. Mouthfuls of food eaten and maternal responsiveness were not significantly increased by the intervention. Mothers in the intervention gave their children more vegetables, and spontaneously recalled more feeding messages at the 5‐month follow‐up. These results provide evidence that self‐feeding and weight gain can improve by targeting specific behaviours, while maternal responsiveness may require more intensive strategies.